Dietary Patterns and Cardiometabolic Outcomes in Diabetes: A Summary of Systematic Reviews and Meta-Analyses - Kahleova, Hana; Salas-Salvadó, Jordi; Rahelić, Dario; Kendall, Cyril Wc; Rembert, Emilie; Sievenpiper, John L (Nutrients, 2019)
The Diabetes and Nutrition Study Group (DNSG) of the European Association for the Study of Diabetes (EASD) conducted a review of existing systematic reviews and meta-analyses to explain the relationship between different dietary patterns and patient-important cardiometabolic outcomes. To update the clinical practice guidelines for nutrition therapy in the prevention and management of diabetes, we summarize the evidence from these evidence syntheses for the Mediterranean, Dietary Approaches to Stop Hypertension (DASH), Portfolio, Nordic, liquid meal replacement, and vegetarian dietary patterns. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach was used to assess the quality of evidence. We summarized the evidence for disease incidence outcomes and risk factor outcomes using risk ratios (RRs) and mean differences (MDs) with 95% confidence intervals (CIs), respectively. The Mediterranean diet showed a cardiovascular disease (CVD) incidence (RR: 0.62; 95%CI, 0.50, 0.78), and non-significant CVD mortality (RR: 0.67; 95%CI, 0.45, 1.00) benefit. The DASH dietary pattern improved cardiometabolic risk factors (P < 0.05) and was associated with the decreased incidence of CVD (RR, 0.80; 95%CI, 0.76, 0.85). Vegetarian dietary patterns were associated with improved cardiometabolic risk factors (P < 0.05) and the reduced incidence (0.72; 95%CI: 0.61, 0.85) and mortality (RR, 0.78; 95%CI, 0.69, 0.88) of coronary heart disease. The Portfolio dietary pattern improved cardiometabolic risk factors and reduced estimated 10-year coronary heart disease (CHD) risk by 13% (-1.34% (95%CI, -2.19 to -0.49)). The Nordic dietary pattern was correlated with decreased CVD (0.93 (95%CI, 0.88, 0.99)) and stroke incidence (0.87 (95%CI, 0.77, 0.97)) and, along with liquid meal replacements, improved cardiometabolic risk factors (P < 0.05). The evidence was assessed as low to moderate certainty for most dietary patterns and outcome pairs. Current evidence suggests that the Mediterranean, DASH, Portfolio, Nordic, liquid meal replacement and vegetarian dietary patterns have cardiometabolic advantages in populations inclusive of diabetes.
Keywords: nutriční terapie; Scandinavian and Nordic Countries; dietary patterns; dieta; cardiometabolic outcomes; Diet, Mediterranean; diabetes mellitus; DASH; vegetarian; Skandinávie a severské státy; DASH dieta; Dietary Approaches To Stop Hypertension; Diabetes Mellitus; Systematic Reviews as Topic; Cardiovascular Diseases; dieta vegetariánská; Nordic; Humans; systematický přehled jako téma; Diet, Vegetarian; liquid meal replacements; Diabetes Complications; komplikace diabetu; metabolické nemoci; MEDLINE; rizikové faktory; Mediterranean; Metabolic Diseases; Diet; cardiovascular disease; strava středomořská; Meta-Analysis as Topic; Risk Factors; diabetes; portfolio; metaanalýza jako téma; Nutrition Therapy; kardiovaskulární nemoci; lidé